Konsepsi Psikologi Tentang Manusia Komunikan: Psikoanalisis, Behaviorisme, dan Humanisme - Ikmal Maulana Akbar (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Communication is a fundamental human need whose success depends not only on the communicator but also on the active role of the communicant as the interpreter of meaning. This article examines humans as communicants from a psychological perspective through a literature study employing three approaches: psychoanalysis, behaviorism, and humanism. The findings reveal that the communicant is an active subject who selects, interprets, and constructs meaning based on subconscious dynamics, social learning processes, and the need for empathy and self-actualization. Message interpretation is influenced by cognitive, affective, behavioral, social, and technological factors. Thus, communication is understood not merely as an exchange of information but as a human process that unites thought, emotion, and moral values.